IoT based agribot for irrigation, fire detection, and monitoring - Prabhat Kumar Panda, Amarjeeth Kumar, Banu Priya S, Bibin A Wilson , Harsha B S (International Journal of Advanced Science and Technology, 2020)
Agriculture and farming play a major role in our economy and our day to day life it may be directly or indirectly. But it is facing problems like water scarcity, high labor cost, improper maintenance, and unexpected fire accidents and this causes huge loose for farmers because of no proper precautions taken on time. This paper is focused on to build an agriculture-based robot which reduces the labor cost, reduce the water wastage, and alert the surrounding people as well as a user on fire accident on the field using IoT Technology. It also provides the user with data of Soil Moisture level, Temperature, Humidity, Fire accidents on the field can be monitored by the user. The robot will move on its pre-determined path and analyze the soil moisture level if the water level is less than threshold level robot waters the soil then move to next plant and continue the process of checking the soil moisture levels and watering at given interval time.